Nutritional and pharmacological correction of calcium and vitamin D deficiency in children - A.E. Abaturov; T.A. Kryuchko; E.L. Kryvusha; O.Ya. Tkachenko (Zaslavsky O.Yu., 2018)
Maintaining the optimal level of calcium in the body of children, especially infants, is an essential condition that is necessary to ensure the state of health. However, the use of natural vitamin D-containing foods does not allow either to prevent the development of vitamin D deficiency or to compensate its deficiency. Taking into account the analysis of evidence-base literature data, the article provides clinical recommendations on the age features of pathogenesis, the prevention and treatment of vitamin D deficiencies, calcium deficiency.